Estrategias de marketing y el posicionamiento de las empresas de calzado de cuero del cantón Guano - Jessica Maribel, Uzhca Padilla (2023)
ABSTRACT: The present research work entitled MARKETING STRATEGIES AND THE POSITIONING OF LEATHER FOOTWEAR COMPANIES IN THE GUANO CANTON, whose main objective was to determine how marketing strategies affect the positioning of the leather footwear companies in the Guano Canton. In the research, a quantitative methodology was used; that is, data collection was carried out by applying a survey of 9 questions to a sample of 264 people; the information obtained was tabulated, generating statistical tables and graphs that allowed us to arrive at to the results extracted from the source. In this way, quantitative data was obtained, which were analyzed and interpreted and became qualitative data. The hypothesis raised in the research has been verified using the chi-square test, where the incidence of the dependent variable marketing strategies and the independent variable positioning were demonstrated. On the other hand, thanks to the applied field research, it was possible to obtain the main result that companies need management of digital tools, which has not allowed them to position themselves in the market and the minds of the consumer. Essential marketing strategies were developed to be applied to obtain successful results and thus generate more significant income.